2012
DOI: 10.5551/jat.12286
|View full text |Cite
|
Sign up to set email alerts
|

Serum Complement C3 Predicts Renal Arteriolosclerosis in Non-Diabetic Chronic Kidney Disease

Abstract: Aim: Complement C3 (C3) is one of the major mediators of inflammation. Serum C3 has been shown to be correlated with the presence of atherosclerosis. We examined whether the serum C3 level might be correlated with the severity of renal arteriolosclerosis in patients with chronic kidney disease (CKD). Methods: Non-diabetic CKD (stages 1-3) patients who underwent renal biopsy were enrolled in this study. Renal arteriolosclerosis was defined by the presence of hyaline changes and vessel wall thickening in the ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 44 publications
0
2
1
Order By: Relevance
“…On the other hand, it was reported that renal arteriolosclerosis was more commonly observed even in the absence of HT, particularly in IgA nephropathy compared with non-IgA nephropathy [34]. A possible explanation would be that renal arteriolosclerosis could be related to an immune-complex reaction and oxidative stress in glomerulonephritis [35,36]. Though we could not examine this relationship in the present study, the progression of arteriolosclerosis could be partially mediated by such factors other than HT.…”
Section: Discussioncontrasting
confidence: 51%
“…On the other hand, it was reported that renal arteriolosclerosis was more commonly observed even in the absence of HT, particularly in IgA nephropathy compared with non-IgA nephropathy [34]. A possible explanation would be that renal arteriolosclerosis could be related to an immune-complex reaction and oxidative stress in glomerulonephritis [35,36]. Though we could not examine this relationship in the present study, the progression of arteriolosclerosis could be partially mediated by such factors other than HT.…”
Section: Discussioncontrasting
confidence: 51%
“…HU has been found to independently predict the progression of kidney disease in diabetic nephropathy 46, 47) , IgA nephropathy 4851) , chronic allograft nephropathy 52) , and CKD 45, 53, 54) . However, although HU has been associated with the presence of kidney arteriolar sclerosis 33, 50, 55, 56) in CKD patients, there is little evidence of an association between UA and disease progression of biopsy-proven nephrosclerosis. In animal models, HU has been found to induce systemic hypertension and afferent arteriolar sclerosis 57, 58) .…”
Section: Discussionmentioning
confidence: 99%
“…Plasma C3, as partially originated from the kidney, could be a marker of ongoing injury of kidney cells, which ultimately results in CKD. Whereas no previous study has explored the association between circulating C3 and CKD in the general population, higher serum C3 levels have been found to be associated with higher levels of urine protein in patients with non-nephrotic CKD [28], and with renal arteriolosclerosis in patients with non-diabetic CKD [35]. Decreased blood C3 levels have been observed in some less common renal diseases (e.g.…”
Section: Discussionmentioning
confidence: 99%